Oncologic Outcomes of Kidney Sparing Surgery versus Radical Nephroureterectomy for the Elective Treatment of Clinically Organ Confined Upper Tract Urothelial Carcinoma of the Distal Ureter - Seisen, Thomas; Nison, Laurent; Remzi, Mezut; Klatte, Tobias; Mathieu, Romain; Lucca, Ilaria; Bozzini, Grégory; Capitanio, Umberto; Novara, Giacomo; Cussenot, Olivier; Compérat, Eva; Renard-Penna, Raphaële; et al. (The Journal of urology, 2016)
PURPOSE: We compared the oncologic outcomes of radical nephroureterectomy, distal ureterectomy and endoscopic surgery for elective treatment of clinically organ confined upper tract urothelial carcinoma of the distal ureter. MATERIALS AND METHODS: From a multi-institutional collaborative database we identified 304 patients with unifocal, clinically organ confined urothelial carcinoma of the distal ureter and bilateral functional kidneys. Rates of overall, cancer specific, local recurrence-free and intravesical recurrence-free survival according to surgery type were compared using Kaplan-Meier statistics. Univariable and multivariable Cox regression analyses were performed to assess the adjusted outcomes of radical nephroureterectomy, distal ureterectomy and endoscopic surgery. RESULTS: Overall 128 (42.1%), 134 (44.1%) and 42 patients (13.8%) were treated with radical nephroureterectomy, distal ureterectomy and endoscopic surgery, respectively. Although rates of overall, cancer specific and intravesical recurrence-free survival were equivalent among the 3 surgical procedures, 5-year local recurrence-free survival was lower for endoscopic surgery (35.7%) than for nephroureterectomy (95.0%, p <0.001) or ureterectomy (85.5%, p = 0.01) with no significant difference between nephroureterectomy and distal ureterectomy. On multivariable analyses only endoscopic surgery was an independent predictor of decreased local recurrence-free survival compared to nephroureterectomy (HR 1.27, p = 0.001) or distal ureterectomy (HR 1.14, p = 0.01). Distal ureterectomy and endoscopic surgery did not significantly correlate to cancer specific or intravesical recurrence-free survival. However, when adjustment was made for ASA(®) (American Society of Anesthesiologists(®)) score, distal ureterectomy (HR 0.80, p = 0.01) and endoscopic surgery (HR 0.84, p = 0.02) were independent predictors of increased overall survival, although no significant difference was found between them. CONCLUSIONS: Because of better oncologic outcomes, distal ureterectomy could be considered the elective first line treatment of clinically organ confined urothelial carcinoma of the distal ureter.
Keywords: karcinom z přechodných buněk; Europe; Female; Laparoscopy; nádory močovodu; ženské pohlaví; Neoplasm Recurrence, Local; přežití bez známek nemoci; Time Factors; časové faktory; laparoskopie; lidé; Elective Surgical Procedures; Evropa; pooperační komplikace; následné studie; míra přežití; Nephrectomy; prognóza; Incidence; retrospektivní studie; Follow-Up Studies; Male; Postoperative Complications; incidence; Carcinoma, Transitional Cell; Ureteral Neoplasms; lokální recidiva nádoru; Ureter; Prognosis; Survival Rate; Disease-Free Survival; ureter; elektivní chirurgické výkony; mortality; mužské pohlaví; kidney; Retrospective Studies; urothelium; carcinoma; nefrektomie; Humans